Reduction of Cerebral and Corpus Callosum Volumes in Childhood‐Onset Systemic Lupus Erythematosus: A Volumetric Magnetic Resonance Imaging Analysis. Issue 9 (25th August 2016) - Tamires Lapa, Aline; Postal, Mariana; Angélica Sinicato, Nailú; Geraldo Ferreira, Weslley; Siqueira Bellini, Bruna; Teixeira Fernandes, Paula; Rittner, Leticia; Marini, Roberto; Cendes, Fernando; Appenzeller, Simone
Abstract : Objective: There have been few studies in which the prevalence of cerebral atrophy in childhood‐onset systemic lupus erythematosus (SLE) was evaluated using magnetic resonance imaging (MRI) volumetric measurements. This study was undertaken to determine the prevalence of cerebral and corpus callosum atrophy in childhood‐onset SLE and to determine the possible relationships between atrophy and clinical, laboratory, and treatment features of the disease. Methods: We included 76 patients with childhood‐onset SLE (69 female and 7 male; median age 16 years) and 66 age‐ and sex‐matched healthy controls. Neurologic manifestations were analyzed according to the American College of Rheumatology (ACR) criteria. These SLE patients were further assessed for clinical and laboratory manifestations of SLE, disease activity (using the SLE Disease Activity Index), damage (using the Systemic Lupus International Collaborating Clinics/ACR Damage Index), and current and cumulative drug exposures. Scans were performed with a Philips 3.0T MRI scanner using a standardized protocol. Results: Childhood‐onset SLE patients had significantly smaller cerebral and corpus callosum volumes than controls (median cerebral volume 1, 067.9 cm 3 versus 1, 172.7 cm 3 and median corpus callosum volume 11.6 cm 3 versus 13.7 cm 3 ; P < 0.001). The presence of structural abnormalities was observed in 42 patients (55.3%) with childhood‐onset SLE. The presence of cerebral atrophy was associated with anticardiolipin antibodies (aCL) ( P = 0.02), anti–double‐stranded DNA ( P = 0.02), and cumulative corticosteroid dose ( P = 0.04). The presence of corpus callosum atrophy was associated with low complement level ( P = 0.006) and acute confusional state ( P = 0.01). Serum levels of S100B or high molecular weight neurofilament and the presence of anti–ribosomal P were not associated with atrophy. Conclusion: Structural brain abnormalities were observed in 55.3% of the patients and were associated with neuropsychiatric manifestations, aCL, and corticosteroid use. To determine permanent neurologic damage, longitudinal studies must be conducted in these patients.